Changes of attracter layout in learning a whole body motor skill - Chen, H.; Chi-Lun, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Based on the dynamic theory, motor learning occurs as the interaction of intrinsic dynamic of system organization and its relevant information that attracts the movement dynamics toward the task goal (Kelso, 1995). The changing nature of attractor was approved by learning the coordination patterns of finger oscillation by Zanone and colleagues (1992). To investigate the evolution of attractor layout of learning the multi-segmental movement skills, the presented study examined the change of behavior dynamics in the process of learning a novel cycling task. Methods: Nine male college students participated as the learners to ride the bike, which with the independently crank, on a roller training plate. As they could ride successfully for at least 10 seconds, the goal relative phase (GRP) between right and left pedal of 180, 90, 270 and 0 degrees were required sequentially in practice sessions under the criterion of each GRP was successfully performed for 5 consecutive trials. There were 20 trails within each 20 seconds in one practice session and totally 8 sessions. Before and after each practice session, the probed tests of 12 trials (3 for each GRP) were implemented. Results:1.A significant Tests×GRPs interaction was observed. Simple main effect showed that the learners had higher error in the pre test than did in the post test for 90 degree GRP. Furthermore, the effect of GRPs was only found in the pre test in which the errors in 180 and 0 degrees RP were lower than those in 270 and 90 degrees RP respectively. 2. Three groups of learners could be classified according to their GRP`s accomplishment. In all, as a new goal was accomplished, the higher r-square value of exponential function fitting could be found. Moreover, most of the learners emerged the 180 degrees RP tendency at the beginning and modified their pedaling movement smoothly as the goal information of 180 was implemented. In contrast, two of the learners revealed the tendency of 90 degrees RP at the beginning of practice and showed the conversely results. 3. Three components could explain approximately all of the variances in which the first component primary reflected the motion of lower body in vertical direction, the second component reflected the motion in forward-backward direction. The third component revealed the minor motion for balancing. The individual difference in whole body movement coordination in learning process was found in the third component. Discussion: Individual difference in learning whole body movement coordination skill was found and could be explained by the mechanism of cooperation/competition effect (Zanone, et. al., 1992). The examination of learning curve showed that the exponential function was found and companied with the better performance in GRP suggesting the dynamics of system toward or around its attractor (Newell, et. al., 2001). The coordination patterns of pedaling and balance construct the motion of whole body segments. Changes of coordination were found in the coordination pattern for balancing.